This I Believe - Pittenger, Lemuel Arthur (Tufts Archival Research Center, 2006)
L.A. Pittenger, president emeritus of Ball State University's Teacher College, describes how his faith was challenged by tragedies and illness, but ultimately strengthened, and he states his beliefs in a creator, in the ultimate order of events, in the thereaputic effects of nature, in the importance of the family, and in the necessity of repaying one's community with service.